Ways and Obstacles to Professional Development of English Language Teachers in International Schools in Jeddah: Perspectives of Teachers and Administrators - Eid, Maysoon Mohmmed; Alharbi, Rabab Saleh (Journal of Educational and Psychological Sciences, 2024)
The aim of this research is to identify ways to enhance the professional development of English language teachers in international schools in Jeddah, from the perspectives of teachers and administrators. Various academic sources such as books, journals, magazines, and scientific studies were consulted to cover the theoretical aspect of the research. The field aspect was achieved through the use of a qualitative approach, where three English language teachers and three administrators were selected to participate in the study.The study revealed several obstacles that hinder the professional development of English language teachers, such as the difficulty of accessing appropriate training and new educational courses. The study recommends promoting a culture of professional development and self-learning among English language teachers through conducting purposeful and regular educational meetings. Additionally, teachers are encouraged to participate in the preparation and evaluation of professional development plans, and to establish a comprehensive annual development plan that covers all relevant areas of English language teaching. Diversifying the programs offered for teacher development and providing more financial support and training for new teachers is also advised.
Keywords: professional development; obstacles to professional development; English language teachers